Firm value and market liquidity around the adoption of common accounting standards - Gao, Pingyang; Jiang, Xu; Zhang, Gaoqing (Journal of Accounting and Economics, 2019)
The adoption of common accounting standards generates both a precision effect and a network effect. When firms use common standards, investors can leverage their knowledge about the standards to process more financial reports. Embedding both effects into the economic framework of Baiman and Verrecchia (1995, 1996), we study the adoption’s effects on reporting precision, firm value, and liquidity of both the switcher and the early adopter. The model helps address the identification challenge and reconcile some existing results in the empirical literature on IFRS adoption. It also generates implications for standardizing disclosure and accounting methods.